THE ASTRONOMICAL CONNECTION OF TERRESTRIAL EVOLUTION: CRUSTAL EFFECTS OF POST-3.8 GA MEGA-IMPACT CLUSTERS AND EVIDENCE FOR MAJOR 3.2+/-0.1 GA BOMBARDMENT OF THE EARTH-MOON SYSTEM - Glikson A.Y. (My University, 2001)
It is accepted that during the Late Heavy Bombardment (LHB-4.2-3.8 Ga) in the Solar system, as preserved on the Moon, the terrestrial upper mantle-crust system was dominated by interactions between internal mantle processes and extraterrestrial impacts, and that following this period, the impact flux decreased by two orders of magnitude, from 4-9x10-13 km-2 year-1 to 3.8-6.3x10-15 km-2 year-1 (for asteroids Dc>=18 km), a rate consistent with a cratering rate of 5.9+/-3.5x10-15 km-2 year-1 estimated for near-Earth asteroids (NEA) and comets. Geology being a geocentric science, the assumption is generally made that from about 3.8 Ga the impact factor can be neglected in the context of models of crustal evolution, including the emergence of early continental nuclei and plate tectonics. This paradigm is questioned in this paper. From the observed minimum number of 6 continental impact structures with Dc>=100 km [Vredefort (300 km); Sudbury (250 km); Chicxulub (170 km); Woodleigh (120 km); Manicouagan (100 km); Popigai (100 km)], assuming an Earth surface occupied by time-integrated >=80% ocean crust since 3.8 Ga, the lower limit of post-LHB impacts is deduced at >=30 craters with Dc>=100 km and >=10 craters with Dc>=250 km. From the lunar crater counts and the present-day asteroid flux the impact incidence was likely to have been higher by an order of magnitude, with a possible decline in the impact frequency of the largest bodies Dp>=20 km. Evidence for maria-scale impact basins in the Archaean emerges from 3.24 Ga-old impact vapor condensation-fallout layers in the Barberton greenstone belt, Transvaal, pointing to multiple oceanic impact basin of Dc>=400 km. This impact cluster falls within error from the c. 3.18 Ga impact peak documented by lunar spherules-suggesting a mid-Archaean impact cataclysm in the Earth-Moon system. Models of crustal evolution need to account for the inevitable magmatic and tectonic consequences of these events, particularly on impacted geothermally active oceanic crust and lithosphere. A combination of the internal heat engine and the impact factors is capable of accounting for the early sialic nuclei, for the spatial and temporal localization of major faulting and rifting events, and for ensuing plate tectonic patterns.
Keywords: Archaean; Precambrian::Archean; Докембрий::Архей